NATIONAL FORESTS IN THE BRAZILIAN AMAZON: DEFORESTATION AND LAND USE PRESSURES (2018-2021) - Gusmão, Luiz Henrique Almeida; Sombra, Daniel Araújo; Messias, Cassiano Gustavo; Camilotti, Vagner Luis (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
The National Forests (FLONAs) of the Brazilian Amazon are crucial protected areas; however, they have faced anthropogenic pressures, primarily from agriculture and mining. This study aims to assess deforestation and contextualize the main anthropogenic pressure vectors present in each FLONA. The research utilized deforestation data from the National Institute for Space Research (INPE) and land use and land cover information from MAPBIOMAS for the period from 2018 to 2021, which were highlighted in thematic maps. The research results identified that: a) FLONAS in southwest Pará, such as Jamanxim, Altamira, and Itaituba II, concentrated most of the deforestation occurring between 2018 and 2021; b) Most FLONAS recorded an increase in deforestation between 2018 and 2021; c) Pastures were identified as the primary drivers of deforestation in FLONAS; d) Southwest Pará and Northern Rondônia concentrated the majority of the most deforested FLONAS by 2021; e) FLONAS facing the most pressure from land use are near highways and agricultural fronts; f) A large portion of FLONAS lost less than 2% of their forest areas; g) There is a significant contrast in forest loss among FLONAS.